Application of the heartwater map-1 branched peptide Elisa on ruminant Sera from Kenya. - Müller, A (University of Edinburgh, 2000)
Heartwater (cowdriosis) is caused by Cowdria ruminamium and transmitted by Amblyomma ticks. To gain further understanding on the epidemiological state of heartwater on smallholder dairy farms in Kenya, a new serological heartwater test (MAP-1 branched peptide ELISA) was first optimised and then applied on bovine sera collected at sites included in an ECF p67 vaccine impact study (ILRl). Further, the suitability of three sites for potential heartwater vaccine studies (EU Concerted Project) was to be assessed. These consisted of two sites of the ECF Project and a third one (Mugie Ranch), where clinical heartwater has been reported in sheep and goats. The ELISA was optimised using 72 bovine sera from experimental Cowdria infections. A cut-off was calculated that included 97% of the 645 'negative' sera from cattle in Kenya. At the sites of the ECF Project, 399 cattle were sampled monthly for five months and a total of 1631 sera tested. The data from the two sites where Amblyomma had been found was pooled to represent the 'exposed' cohort, the others to represent the 'unexposed' cohort. The serological results of the cohorts were compared and expressed as relative risks and risk differences. Single and multiple seroconversions to the MAP-I branched were observed for both cohorts. Findings suggest that only one in three animals of the exposed cohort seroconverted due to exposure to Cowdria. An incidence rate of 11 seroconversions per 100 animals months was calculated for the exposed cohort. The results of the 110 sera from Mugie are presented without data analysis. The findings and underlying assumptions to the calculations are discussed in relation to the present knowledge on heartwater. It is concluded that the MAP-1 branched peptide ELISA has not been sufficiently validated to permit a full understanding and characterization of the epidemiological state of heartwater at the sites where an EFC vaccine might be applied or in terms of assessment of sites for potential heartwater vaccine studies.